2020
DOI: 10.1097/md.0000000000021877
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine Yanghe decoction for knee osteoarthritis

Abstract: Background: Chinese herbal medicine (CHM) has been widely used to treat knee osteoarthritis (KOA), among which Yanghe decoction (YHD) is one of the commonly used prescriptions. The purpose of this study is to evaluate the effectiveness and safety of YHD in the treatment of KOA. Methods: Six databases, including Embase, PubMed, the Cochrane Library, the China National Knowledge Infrastructure, Wanfang Database and Chinese Science and Technology Periodical Database will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As an effective method for preventing and treating diseases, TCM has been increasingly used worldwide in the past decades [6]. Yanghe decoction is a famous formula consisting of Rehmannia, deer horn gum, cinnamon, rue, Ephedra, ginger charcoal, and licorice [7]. It has the effect of warming yang and nourishing blood and dispersing cold and moving stagnation.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective method for preventing and treating diseases, TCM has been increasingly used worldwide in the past decades [6]. Yanghe decoction is a famous formula consisting of Rehmannia, deer horn gum, cinnamon, rue, Ephedra, ginger charcoal, and licorice [7]. It has the effect of warming yang and nourishing blood and dispersing cold and moving stagnation.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of joint pain described in the classic literature are consistent with KOA symptoms, including knee swelling [ 17 , 18 ]. The application of acupuncture has a long clinical history in the treatment of bone diseases [ 19 ]. Acupuncture can help relieve pain, relax tendons, activate meridians, and eliminate aseptic inflammation and local edema of knee joint, as well as dredge meridians in patients [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 TCM considers BT an autoimmune disease. 7,8 YHD may regulate the immune system to treat BT. However, the therapeutic effect of YHD on BT and the corresponding mechanism of action of YHD need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that modified YHD can be used to treat ankylosing spondylitis treatment, 7 and YHD is regarded as a safe and effective alternative therapy for preventing chondrocyte apoptosis, and as an antiinflammatory in treating knee osteoarthritis. 8 TCM considers BT an autoimmune disease. 7,8 YHD may regulate the immune system to treat BT.…”
Section: Introductionmentioning
confidence: 99%